Análise bibliométrica do reaproveitamento de resíduos refratários - Matos, Kelvyn Gomes (Universidade Federal de São Carlos, 2024)
The recycling process of refractory materials involves the collection, treatment, and reintroduction of these materials into the production chain after their initial use in applications that require resistance to high temperatures, such as industrial furnaces and metallurgical systems. Once discarded, these ceramics undergo specific techniques for impurity removal, fragmentation, and shaping, aiming to obtain a recycled product with properties suitable for reintegrating into new processes. However, there is currently a substantial lack of information in the specialized literature regarding the reuse of refractory materials. This partly reflects the absence of a significant economic or environmental incentive that promotes recycling practices among manufacturers. In this context, the present study aimed to examine current trends in the reuse of refractory waste from 1992 to 2023, highlighting emerging themes in this area of study. To achieve this, a systematic literature review was conducted, providing an overview of the current state of knowledge, along with a bibliometric analysis of metadata, which allowed for tracing trends in available publications. From the analyzed data, it was observed that the number of publications focused on refractory recycling has significantly increased in recent years. The main journals publishing works on the subject are related to innovation in construction and materials, covering interdisciplinary research. China plays a central role in commercial leadership and research on refractory waste recycling, demonstrating strong interest and increasing investment in research by the country. Brazil, on the other hand, has dedicated efforts to advancing studies and technologies for refractory reuse, with active participation from the private industry.
Bibliometric analysis of refractory waste reuse
Keywords: Reaproveitamento; Refratário; Reciclagem; Resíduos; Seleção de materiais; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS